2014
DOI: 10.1167/iovs.14-14002
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Molecular Pathogenesis of Thyroid-Associated Ophthalmopathy

Abstract: Graves' disease (GD) is a common autoimmune condition. At its core, stimulatory autoantibodies are directed at the thyroid-stimulating hormone receptor (TSHR), resulting in dysregulated thyroid gland activity and growth. Closely associated with GD is the ocular condition known as thyroid-associated ophthalmopathy (TAO). The pathogenesis of TAO remains enigmatic as do the connections between the thyroid and orbit. This review highlights the putative molecular mechanisms involved in TAO and suggests how these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 195 publications
3
156
1
9
Order By: Relevance
“…In early stages of the disease, connective tissue, orbital fat and muscles are infiltrated by T lymphocytes, mast cells and plasmatic cells. It was found that orbital fibroblasts are the main target of the autoagression process [16]. Activation of fibroblasts leads to their proliferation and differentiation into myofibroblasts and adipocytes and secondary production of glycosaminoglycans, chemokines and cytokines, which enhance inflammatory reaction in the orbital tissues [17,18].…”
Section: Pathogenesis Of Thyroid-associated Ophthalmopathymentioning
confidence: 99%
“…In early stages of the disease, connective tissue, orbital fat and muscles are infiltrated by T lymphocytes, mast cells and plasmatic cells. It was found that orbital fibroblasts are the main target of the autoagression process [16]. Activation of fibroblasts leads to their proliferation and differentiation into myofibroblasts and adipocytes and secondary production of glycosaminoglycans, chemokines and cytokines, which enhance inflammatory reaction in the orbital tissues [17,18].…”
Section: Pathogenesis Of Thyroid-associated Ophthalmopathymentioning
confidence: 99%
“…Graves' orbitopathy (GO) is the extrathyroidal manifestation of Graves' disease characterized by an autoimmune inflammation resulting in an increased volume of the orbital connective tissue and enlargement of the extraocular muscles (Bahn 2010, Wang & Smith 2014. Orbital fibroblasts (OFs) are the main target cells in GO due to their expression of autoantigens specific to GO (Otto et al 1996, Bahn 2010, Wang & Smith 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Orbital fibroblasts (OFs) are the main target cells in GO due to their expression of autoantigens specific to GO (Otto et al 1996, Bahn 2010, Wang & Smith 2014. Macrophages, T and B lymphocytes, and mast cells infiltrate the orbit and activate the OFs (Bahn 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Activating autoantibodies targeting the TSHR and infiltrating lymphocytes cause thyroid gland dysfunction by driving overproduction of thyroid hormone and potentiating inflammation. Despite progress in understanding the endocrine manifestations of GD, the pathogenesis of thyroidassociated ophthalmopathy (TAO) and the role of the TSHR remain largely unknown (3). Orbital tissues from patients with TAO express several putative autoantigens, including the TSHR (4), which may mediate immune activation.…”
Section: Introductionmentioning
confidence: 99%